Persepsi Bunuh Diri Pada Kalangan Usia Muda di Kecamatan Sei Beduk Kota Batam - Rafles Simanjuntak; Siti Arieta; Rahma Syafitri (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
This academic writing delves into the dynamic interplay between the younger generation and their societal engagement, emphasizing its relevance in influencing decision-making processes and the contemplation of suicide, as postulated by Durkheim. The research design adopts a quantitative approach, aligned with the tenets of positivist philosophy. Within this framework, a specific population or sample is scrutinized, and data is collected through research instruments, subsequently subjected to quantitative/statistical analysis. The study's focus is on the Young Adult Cohort, aged 17 to 30 years, within the Sei Beduk Subdistrict of Batam City. The selected respondents for this study amount to 200 individuals, encompassing various demographic attributes such as gender, age, highest education level, and occupation. Young adults frequently confront intricate physical, emotional, and social challenges. Prominent economic factors at the individual level encompass financial difficulties, including the inability to settle debts, both short-term and long-term unemployment, and underemployment. Amidst the backdrop of adolescent social interactions, a myriad of issues surfaces, necessitating a robust social support system. Such support is procurable from family environments, friends, and broader social circles.